Carbon-supported metal catalyst and preparation method thereof
By using a combined annealing technology of acetylacetone salt, air and hydrogen argon atmosphere in the fuel cell catalyst, platinum-based intermetallic compound nanoparticles wrapped in carbon layer were formed, and the problems of high platinum dosage and unstable catalyst activity were solved, and a catalyst with high order and excellent activity was achieved.
Patent Information
- Application Number
- CN202510099772.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-22
AI Technical Summary
Among the existing fuel cell catalysts, the amount of platinum is high and the preparation method is complex, resulting in high application cost and unstable catalyst activity.
The first annealing in an air atmosphere by using acetylacetone salt of platinum and transition metals followed by a two-step gas phase reduction under a hydrogen-argon atmosphere to form platinum-based intermetallic compound nanoparticles wrapped by a controllable carbon layer to avoid particle agglomeration and improve the order and activity of the catalyst.
The high order and excellent activity of the platinum-based intermetallic compound catalyst are achieved, the amount of platinum is reduced, the preparation process is simplified, and the stability and electrochemical properties of the catalyst are improved.
Smart Images

Figure CN119833656A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of fuel cell technology, and mainly to a carbon-supported metal catalyst and a preparation method thereof. Background Art
[0002] The fuel cells proposed so far can effectively convert hydrogen into electrical energy, and have good application prospects in the fields of energy conversion devices and heavy truck driving. Platinum and platinum-based alloys are necessary catalyst materials for proton exchange membrane fuel cells, and are also the main factors affecting the conversion capacity and application cost of proton exchange membrane fuel cells. However, the amount of platinum used in commercial fuel cell vehicles is relatively high. For example, the platinum loading in Toyota Mirai is about 36 g. The high application cost has become the main factor limiting the widespread use of proton exchange membrane fuel cells.
[0003] At present, an effective strategy to reduce the platinum loading is to alloy Pt with the first-row transition metals, that is, to add smaller transition metal atoms to the Pt-based alloy to cause beneficial strain and alloy effects to increase the oxygen reduction reaction (ORR) rate of the platinum alloy catalyst. For platinum-based alloy catalysts, the order of the catalyst generally increases with the increase of temperature, and the order is positively correlated with the activity of the catalyst. However, high-temperature annealing is often required to achieve a higher atomic order, and the high-temperature annealing treatment will inevitably accelerate metal sintering, causing nanoparticles to agglomerate and reduce activity. At present, many preparation methods have been developed to prepare fine nanoparticles, especially nanoparticles of platinum-based catalyst materials used in fuel cells, such as coating with polymer or metal oxide protective shells before annealing to limit the size of the particles, or preparing by small molecule-assisted impregnation, etc., but these methods are cumbersome to operate, the thickness of the protective shell is difficult to control, and it is easy to affect the activity of the platinum-based catalyst. Therefore, the existing technology still needs to be improved and developed. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the purpose of the present application is to provide a carbon-supported metal catalyst and a preparation method thereof, aiming to solve the problem that the existing method of controlling the agglomeration of metal particles in the catalyst is cumbersome to operate and easily affects the activity of the catalyst.
[0005] The technical solution of this application is as follows: In a first aspect, the present application provides a method for preparing a carbon-supported metal catalyst, which comprises the following steps: Platinum acetylacetonate, acetylacetonate of a transition metal and a carbon material are dispersed in a solvent, the solvent is removed by drying to obtain a precursor, and a mixture is obtained after a first annealing in an air atmosphere; The mixture is annealed for a second time in a hydrogen and argon atmosphere, acid-washed after cooling, washed and dried, and annealed for a third time in a hydrogen and argon atmosphere to obtain the carbon-supported metal catalyst.
[0006] The present application uses platinum and acetylacetonate of transition metals, directly annealing in an air atmosphere after uniform impregnation, and then performs a two-step gas phase reduction in a hydrogen and argon atmosphere to obtain platinum-based intermetallic compound nanoparticles wrapped by an adjustable carbon layer, which can effectively prevent particle agglomeration and produce highly ordered catalyst particles with fine and uniform distribution and excellent activity. Carbon-supported metal catalysts.
[0007] Furthermore, the temperature of the first annealing is 100-500° C., and the annealing time is 5-500 min; The weight loss rate of the mixture before and after the first annealing is 1-50%wt.
[0008] In the present application, a carbon layer is formed by acetylacetone group. By controlling the temperature and weight loss rate of the first annealing, the thickness of the subsequently formed carbon layer and the wrapping performance of the reduced metal particles can be controlled, which is beneficial to improving the catalytic effect of the catalyst.
[0009] Furthermore, the temperature of the first annealing is 176°C, and the annealing time is 20-40min; The weight loss rate of the mixture before and after the first annealing is 1-30%wt.
[0010] In the present application, the acetylacetonate group is adjusted to improve the catalytic activity at 176° C. and a weight loss rate of no more than 30%.
[0011] Furthermore, the second annealing condition is annealing at 400-1100° C. for 10 min-8 h.
[0012] In the present application, by annealing in an argon-hydrogen atmosphere, the acetylacetone group can decompose and form a carbon layer to wrap the reduced nano-metal particles, effectively preventing the particles from agglomerating.
[0013] Furthermore, the pickling condition is pickling in sulfuric acid with a concentration of 0.1-1 mol / L at 60° C. for 12 hours.
[0014] Furthermore, the third annealing condition is annealing at 100-500° C. for 10 min-6 h.
[0015] In the present application, by performing the third annealing, the strength of the metal structure between platinum and the transition metal can be stabilized and the stability can be improved.
[0016] Further, the carbon material includes graphitized carbon or commercial carbon material; The graphitized carbon is prepared by heating an amorphous carbon material at 1200-3000° C. for 10 min-6 h in an inert atmosphere or a nitrogen atmosphere, and then naturally cooling to room temperature; The commercial carbon material is one of Vulcan XC72, KB300, KB600, BP 2000 or Toray carbon.
[0017] Furthermore, the acetylacetonate of the transition metal is one or more of acetylacetonate iron, acetylacetonate nickel, acetylacetonate molybdenum, acetylacetonate vanadium, acetylacetonate copper, acetylacetonate manganese, acetylacetonate zinc, acetylacetonate titanium, acetylacetonate tungsten, acetylacetonate chromium and acetylacetonate zirconium.
[0018] Furthermore, the platinum loading in the carbon-supported metal catalyst is 1-60wt%.
[0019] In a second aspect, the present application also provides a carbon-supported metal catalyst, which includes a carbon carrier distributed with metal nanoparticles, and the surface of the metal nanoparticles is coated with a carbon layer; The carbon carrier is a solid nanoparticle or a porous continuous structure, and the particle size of the solid nanoparticle is 1nm-300μm; The particle size of the metal nanoparticles is 1-20 nm; The pore structure in the carbon layer is one of loose porous, microporous or closed non-porous; The coating is one of no coating, partial coating or full coating; The thickness of the carbon layer is 0.001nm -50nm; The number of the carbon layers is 0-50.
[0020] Beneficial effect: The present application uses platinum and acetylacetonate of transition metals, directly annealing in an air atmosphere after uniform impregnation, and then performs a two-step gas phase reduction in a hydrogen and argon atmosphere to obtain platinum-based intermetallic compound nanoparticles wrapped by an adjustable carbon layer, which can effectively prevent particle agglomeration and can produce highly ordered catalyst particles with fine and uniform distribution and excellent activity. Carbon-supported metal catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1a This is an electron microscope image of the particle distribution of the graphitized carbon-supported metal catalyst of Example 1 of the present application.
[0022] Figure 1b This is an electron microscope image of the graphitized carbon-supported metal catalyst particles of Example 1 of the present application.
[0023] Figure 2This is the XRD test result of the graphitized carbon-supported metal catalyst of Example 1 of the present application.
[0024] Figure 3 This is the TGA curve of the precursor of Example 1 of the present application obtained by heating the temperature in air at 5°C / min.
[0025] Figure 4a This is an electron microscope image of the particle distribution of the graphitized carbon-supported metal catalyst annealed in an air atmosphere at 152°C in Example 2 of the present application.
[0026] Figure 4b This is an electron microscope image of the particle distribution of the graphitized carbon-supported metal catalyst annealed in an air atmosphere at 164°C in Example 2 of the present application.
[0027] Figure 4c This is an electron microscope image of the particle distribution of the graphitized carbon-supported metal catalyst annealed in an air atmosphere at 188°C in Example 2 of the present application.
[0028] Figure 4d ORR polarization curves of graphitized carbon-supported metal catalysts annealed in air atmosphere at 152° C., 164° C., 176° C., and 188° C., respectively, in Examples 1 and 2 of the present application.
[0029] Figure 5 These are the XRD test results of the graphitized carbon-supported metal catalyst prepared by annealing in an air atmosphere at 152° C., 164° C., and 188° C. in Example 2 of the present application.
[0030] Figure 6 This is an electron microscope image of the particle distribution of the graphitized carbon-supported metal catalyst of Example 3 of the present application.
[0031] Figure 7 This is the XRD test result of the graphitized carbon-supported metal catalyst of Example 3 of the present application.
[0032] Figure 8 This is an electron microscope image of the particle distribution of the KB600 supported platinum-based intermetallic compound catalyst of Example 4 of the present application.
[0033] Fig. 9 This is the XRD test result of the KB600 supported platinum-based intermetallic compound catalyst of Example 4 of the present application.
[0034] Fig.10a This is an electron microscope image of the particle distribution of the catalyst of Comparative Example 1 of the present application.
[0035] Fig.10b This is an electron microscope image of the catalyst particles of Comparative Example 1 of the present application.
[0036] Fig.11This is the XRD test result of the catalyst of Comparative Example 1 of the present application.
[0037] Fig.12 ORR polarization curves of the graphitized carbon-supported metal catalyst of Example 1 of the present application and the commercial platinum-carbon catalyst of Comparative Example 2.
[0038] Fig.13 This is a diagram of the ORR polarization curves of the KB600-supported platinum-based intermetallic compound catalyst of Example 4 of the present application and the commercial platinum-carbon catalyst of Comparative Example 2.
[0039] Fig.14 This is a diagram of the ORR polarization curves of the graphitized carbon-supported metal catalyst of Example 1 of the present application and the graphitized carbon-supported catalyst of Comparative Example 1.
[0040] Fig.15 This is a bar chart comparing the specific activity values of Example 1, Comparative Example 1 and Comparative Example 2 of the present application. DETAILED DESCRIPTION
[0041] The present application provides a carbon-supported metal catalyst and a preparation method thereof. To make the purpose, technical solution and effect of the present application clearer and more specific, the present application is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0042] At present, platinum-based intermetallic compound catalysts usually need to be annealed at high temperature to obtain a higher degree of order, and the degree of order of platinum-based intermetallic compound catalysts is positively correlated with their catalytic performance. However, high-temperature annealing will inevitably accelerate metal sintering, produce larger crystallites, and cause the nanoparticles of platinum-based intermetallic compound catalysts to agglomerate, reducing the specific surface area and mass specific activity, thereby greatly reducing the activity and stability of the catalyst.
[0043] To address this problem, the present application provides a method for preparing a carbon-supported metal catalyst, which comprises the following steps: S1, dispersing platinum acetylacetonate, acetylacetonate of a transition metal and a carbon material in a solvent, drying and removing the solvent to obtain a precursor, and then annealing for the first time to obtain a mixture; S2. annealing the mixture for a second time in a hydrogen and argon atmosphere, acid washing after cooling, washing and drying, and annealing the mixture for a third time in a hydrogen and argon atmosphere to obtain a carbon-supported metal catalyst.
[0044] The present application uses platinum and acetylacetonate of transition metals, directly annealing in an air atmosphere after uniform impregnation, and then performs a two-step gas phase reduction in a hydrogen and argon atmosphere to obtain platinum-based intermetallic compound nanoparticles wrapped by an adjustable carbon layer, which can effectively prevent particle agglomeration and produce highly ordered catalyst particles with fine and uniform distribution and excellent activity. Carbon-supported metal catalysts.
[0045] The ratio of platinum to transition metal is 1:0.1-10, preferably 1:1-1.2.
[0046] Specifically, in the present application, by directly using acetylacetonate of platinum and transition metal, the acetylacetonate group therein is directly used as the carbon layer raw material. The acetylacetonate group can decompose and recombine to form a carbon layer to wrap the platinum-based intermetallic compound nanoparticles to limit the occurrence of agglomeration, thereby obtaining a catalyst material with uniformly distributed nanoparticles and high activity.
[0047] In step S1, after platinum acetylacetonate, acetylacetonate of transition metal and graphitized carbon are dispersed in a solvent, they can be uniformly mixed by ultrasonication and then dried by rotary evaporation.
[0048] Furthermore, the carbon material includes graphitized carbon or commercial carbon material. Among them, graphitized carbon is prepared by keeping amorphous carbon material at 1200-3000°C for 10min-6h in an inert atmosphere or a nitrogen atmosphere, and then naturally cooling to room temperature. Specifically, graphitized carbon can also be replaced with a more commonly used commercial carbon material on the market according to demand, such as Vulcan XC72, KB300 (Ketjen Black 300), KB600 (Ketjen Black 600), BP 2000 or Toray carbon. Among them, the carbon material is preferably graphitized carbon, which has stronger corrosion resistance than other carbon materials in a high-temperature acidic environment, but at the same time, graphitized carbon has fewer surface defects and cannot effectively load metal nanoparticles, so the traditional chloroplatinic acid impregnation will cause the particles to easily agglomerate, and through the adjustment of this application, the problem of particle agglomeration can be effectively addressed.
[0049] In step S1, the solvent can be acetone, and the amount of acetone ranges from 6 to 10 ml. The amount can be selected according to the different carbon materials. The specific standard can be 150 mg of carbon material corresponding to 6 to 10 ml of acetone. Since different carbon materials have different volumes after being immersed in solvents, acetone is required to immerse the carbon material for dispersion. In the present application, acetylacetonate and carbon material are uniformly dispersed in acetone to obtain a uniform solution, so that uniformly distributed nanoparticles can be subsequently reduced on the carbon carrier by gas phase reduction.
[0050] Among them, acetone is removed by rotary drying. Acetone, as a solvent of the precursor, plays a dispersing role and does not participate in the synthesis of the material. If it is not removed, it will cause uneven dispersion of the precursor, thereby causing agglomeration of particles.
[0051] Furthermore, the first annealing condition is annealing in an air atmosphere at a temperature of 100-500°C, and the annealing time is 5-500min. At present, the method of introducing the carbon layer through general organic ligands requires the addition of other substances, which may introduce other impurities, and the steps will be more cumbersome, increasing the cost. The present application uses acetylacetonate as the organic metal salt of the target metal, the composition is relatively simple, and the carbon layer formed by the acetylacetonate group will be simpler and purer.
[0052] Preferably, the first annealing condition is annealing in an air atmosphere at a temperature of 176°C, and the annealing time is 20-40min. Specifically, the platinum-based intermetallic compound nanoparticles are wrapped by a carbon layer to avoid agglomeration under high-temperature annealing conditions, but the wrapped carbon layer cannot be too thick, otherwise it will affect the catalytic effect of the catalyst. In the present application, controlling the first annealing temperature at 176°C is proposed for the acetylacetonate group. By performing a pre-oxidation intervention pretreatment in an air atmosphere at 176°C, the subsequent decomposition and recombination of the acetylacetonate group can be regulated, and the formed carbon layer can be optimized. The catalyst wrapped by the carbon layer can be evenly distributed on the graphitized carbon carrier, which is conducive to obtaining a carbon-supported metal catalyst with excellent oxygen reduction reaction performance.
[0053] Further, the weight loss rate of the mixture before and after the first annealing is 1-50%wt. Among them, the weight loss rate can be controlled according to the time and temperature of the annealing treatment. Carbon will react at high temperature. Generally, the longer the time or the higher the temperature, the less carbon is left, and the higher the weight loss rate. More specifically, annealing in an air atmosphere will oxidize part of the acetylacetone group, affecting the content of the carbon layer on the surface. The weight loss rate of the mixture before and after the first annealing will affect the performance of the carbon layer. If the weight loss is too low, the carbon layer is too thick, and the exposed active sites will be less. Increasing the weight loss rate will cause the carbon layer to become thinner or even unable to form, which will cause the particles to agglomerate and reduce the performance.
[0054] More preferably, the weight loss rate of the mixture before and after the first annealing is not higher than 30%wt. When the weight loss rate exceeds 30%wt, the particles tend to become larger, which is more likely to affect the catalytic performance. By controlling the weight loss rate within an appropriate range, a better balance between active sites and carbon layer thickness can be achieved.
[0055] Further, the condition of the second annealing is annealing at 400-1100 ℃ for 10min-8h, preferably 700 ℃, and the annealing time is 6h. In the present application, by carrying out high temperature annealing under a hydrogen-argon atmosphere, the acetylacetonate platinum in the mixture and the acetylacetonate of the transition metal can be reduced to nano metal particles in situ, and then at high temperature, the acetylacetonate group is heated and decomposed and reorganized, and then through the continuous maintenance of high temperature and the continuous outflow of the hydrogen-argon atmosphere, the acetylacetonate group decomposed at high temperature is decomposed into small molecular fragments and then forms a carbon layer while wrapping the nano metal particles, limiting the growth of particles, effectively preventing the agglomeration or sintering of particles, and the nano metal particles reduced at the same time can also obtain a high degree of order at high temperature, and then obtain particles uniformly distributed and have a catalyst material with high activity. Simple operation, no other impurities and elements are introduced, and the degree of order of the alloy is higher, improving stability and performance, particles are smaller, and performance is also better.
[0056] Furthermore, the pickling condition is to pickle in sulfuric acid with a concentration of 0.1-1 mol / L, preferably 0.25 mol / L, at 60° C. for 12 h. In the present application, the removal of additional transition metal atoms on the surface of the metal particles by pickling is beneficial to improving stability.
[0057] Furthermore, the third annealing condition is annealing at 100-500° C. for 10 min-6 h, preferably 200° C. for 1.5 h. In the present application, the third annealing can stabilize the metal structure strength between platinum and the transition metal and improve the stability.
[0058] The argon-hydrogen ratio in the hydrogen-argon atmosphere during the second and third annealing can be maintained within a safe range of 99:1-80:20.
[0059] Further, the transition metal acetylacetonate is one or more of acetylacetonate iron, acetylacetonate nickel, acetylacetonate molybdenum, acetylacetonate vanadium, acetylacetonate copper, acetylacetonate manganese, acetylacetonate zinc, acetylacetonate titanium, acetylacetonate tungsten, acetylacetonate chromium and acetylacetonate zirconium. Preferably, the transition metal acetylacetonate is preferably cobalt acetylacetonate. Platinum-cobalt alloy has higher performance among the currently reported platinum-based alloys and is also an alloy choice used more in alloy catalysts. The use of platinum-cobalt alloy is conducive to improving the performance of the catalyst.
[0060] Specifically, using chloroplatinic acid as a platinum source, decomposition at high temperature will produce agglomeration. At present, metal particles are generally first reduced at low temperature, and then some substances are added to limit the agglomeration of the particles before high-temperature treatment. These added substances will still remain after high-temperature annealing, so further treatment is often required. In addition, this process will also affect the performance of the formed carbon layer, which will affect the diffusion of the solution on the catalyst surface during use and affect the catalytic effect. However, the present application uses acetylacetonate as a metal source, and the acetone used is extremely volatile and will not volatilize. Through high-temperature treatment with graphitized carbon, the acetylacetonate decomposes at high temperature, and the decomposed substances will form a carbon layer to wrap and limit the agglomeration of the particles. Relative to the existing preparation method, the preparation can be completed in a shorter operation step, the synthesis is simple, and the cost is lower.
[0061] Furthermore, the platinum loading in the carbon-supported metal catalyst is 1-60wt%, preferably 5-60wt%.
[0062] The present application also provides a carbon-supported metal catalyst, which includes a carbon carrier on which metal nanoparticles are distributed and loaded, and the surface of the metal nanoparticles is coated with a carbon layer.
[0063] Specifically, in the provided carbon-supported metal catalyst, metal nanoparticles are uniformly distributed on the carbon carrier, and each metal particle on the carbon carrier is wrapped by a carbon layer.
[0064] Furthermore, the carbon carrier can be one of solid nanoparticles or porous continuous structures, and the particle size of the solid nanoparticles is 1nm-300μm. The solid nanoparticles or porous continuous structure carbon carriers include commercial carbon materials and graphitized carbon.
[0065] Further, the particle size of the metal nanoparticles is 1-20 nm, preferably 3-5 nm. Specifically, the metal nanoparticles can be one or more metal compounds selected from platinum, iron, nickel, molybdenum, vanadium, copper, manganese, zinc, titanium, tungsten, chromium, and zirconium, preferably platinum nanoparticles and platinum-based metal compound nanoparticles. The particle size of the metal nanoparticles can be measured by observing the STEM image of the carbon-supported metal catalyst or the XRD test results.
[0066] Furthermore, the pore structure in the carbon layer can be one of loose porous, microporous or closed non-porous. Furthermore, the pore structure in the carbon layer is preferably loose porous, with a larger electrochemical contact area, which is conducive to improving the electrochemical performance.
[0067] Specifically, the distribution of pores in the wrapped carbon layer can be observed through the STEM image of the carbon-loaded metal catalyst, or it can be judged based on the electrochemical data. A loose and porous structure has a good electrochemical contact area, so the excellent electrochemical performance also reflects that the coated carbon layer has a loose and porous structure.
[0068] Furthermore, the coating can be uncoated, partially coated or fully coated, preferably fully coated. The coating degree of the carbon layer can be observed by STEM images of the carbon-supported metal catalyst.
[0069] Furthermore, the thickness of the carbon layer is 0.001-50 nm, preferably 0.01 nm-3 nm. The thickness of the carbon layer can be observed through the STEM image of the carbon-supported metal catalyst.
[0070] Furthermore, the number of carbon layers is 0-50, preferably 1-2. The number of carbon layers can be observed through the STEM image of the carbon-supported metal catalyst.
[0071] Preferably, the provided carbon-supported metal catalyst can also be prepared by the preparation method of the carbon-supported metal catalyst as described above. The preparation method provided by the present application can maintain the structure and properties of the carbon carrier, and can be prepared on the required carbon carrier as needed. The metal nanoparticles of the prepared carbon-supported metal catalyst are fully coated with a loose and porous carbon layer, the thickness of the carbon layer is less than 3nm, and the number of carbon layers is less than 2 layers. The thickness and number of carbon layers formed by acetylacetone groups can be regulated by controlling the annealing conditions. The particle size of the metal nanoparticles is 1-20nm. The carbon-supported metal catalyst has good catalytic performance, high stability and high cycle performance.
[0072] The invention is further described below by means of specific examples.
[0073] Example 1 The graphitized carbon-supported platinum-cobalt intermetallic compound of Example 1 of the present application comprises the following steps: Platinum acetylacetonate, cobalt acetylacetonate and 150 mg of graphitized carbon were dispersed in 7 ml of acetone by ultrasonication; the platinum loading was controlled to be 30 wt % and the cobalt loading was controlled to be 30 wt %, and the precursor of Example 1 was obtained after drying and removing acetone, and then the precursor was annealed for the first time at 176° C. in an air atmosphere, and a mixture was obtained after annealing for 20 min; The mixture was annealed for a second time in a hydrogen and argon atmosphere at 700°C for 6 hours, and after cooling, it was placed in 0.25 mol / L sulfuric acid and pickled at 60°C for 12 hours. After pickling, the catalyst was washed with deionized water and then dried in a vacuum oven at 65 degrees. After drying, it was annealed for a third time in a hydrogen and argon atmosphere at 200°C for 1.5 hours to obtain the graphitized carbon-supported platinum-cobalt intermetallic compound catalyst of Example 1.
[0074] The graphitized carbon used in Example 1 was prepared by keeping the amorphous carbon material at 1800° C. for 75 min in an argon atmosphere and naturally cooling it to room temperature.
[0075] The particle distribution and electron microscope images of the graphitized carbon supported platinum-cobalt intermetallic compound catalyst of Example 1 are shown in FIG. Figure 1a and Figure 1b As shown, it can be seen that the particles are evenly distributed on the surface of graphitized carbon, the carbon carrier is loaded with platinum-cobalt intermetallic compound particles, and a thin layer of carbon layer is completely coated on the surface of the particles, and the thickness of the carbon layer is less than 2.5nm. Figure 2 As shown, XRD test shows that Pt1Co1 (a platinum-cobalt intermetallic compound with a platinum-cobalt atomic ratio of 1 / 1) was successfully prepared. And by observing the electron microscope photos and XRD test results, it can be concluded that the particle size of the platinum-cobalt intermetallic compound particles coated with a carbon layer is 4-5 nm. The TGA curve obtained by heating the precursor containing acetylacetonate and graphitized carbon in air at 5°C / min is as follows Figure 3 shown.
[0076] Example 2 The preparation method of the graphitized carbon supported platinum-cobalt intermetallic compound catalyst of Example 2 is basically the same as that of Example 1, except that the precursor of Example 2 is set in triplicate, and the temperatures of the first annealing are set to 152°C, 164°C and 188°C, respectively, and are set to Example 2a, Example 2b and Example 2c, respectively. The graphitized carbon supported platinum-cobalt intermetallic compound catalyst prepared in Example 2 is subjected to STEM test and XRD test. The particle distribution photographed by STEM is shown in FIG. Figure 4a , Figure 4b and Figure 4c As shown, it can be seen that the particles are evenly distributed on the surface of graphitized carbon, the carbon carrier is loaded with platinum-cobalt intermetallic compound particles, and a thin layer of carbon layer is completely coated on the surface of the particles. The performance of the carbon layer is slightly different. The graphitized carbon loaded platinum-cobalt intermetallic compound catalysts prepared in Example 1 and Example 2 were tested for activity. The oxygen reduction reaction test was carried out in an electrochemical cell in an oxygen-saturated 0.1M perchloric acid solution at a scan rate of 20mV s -1 The ORR performance tests of Example 1 and Example 2 are as follows: Figure 4d As shown in FIG. 1 , it can be found that the ORR performance of Example 1 annealed at 176° C. is relatively good. Figure 5 As shown. Through observation, it can be found that as the temperature increases, the particles become larger. At the same time, the main peak shows the peak of solid solution. The peak that appears has a small bifurcation, which may be that some particles are not fully combined. It can be seen that the temperature of the first annealing will also affect the bonding effect of the platinum-based metal. As the temperature increases, the effect of the carbon layer on limiting the growth of particles decreases, resulting in larger particles.
[0077] Example 3 The preparation method of the graphitized carbon supported platinum-cobalt intermetallic compound catalyst of Example 3 is basically the same as that of Example 1, except that the second annealing condition of Example 3 is to keep the temperature at 700°C for 2h in a hydrogen-argon atmosphere. The graphitized carbon supported platinum-cobalt intermetallic compound catalyst of Example 3 is subjected to STEM test and XRD test. The particle distribution photographed by STEM is as follows: Figure 6 As shown in the figure, it can be seen that the distribution of particles on the graphitized carbon surface is slightly poor, the carbon carrier is loaded with platinum-cobalt intermetallic compound particles, and the surface of the particles is fully covered with a carbon layer. Figure 7 The electron microscope shows that the particles are evenly distributed, but the XRD test shows a peak of solid solution, which shows that the annealing time is only two hours, and the order is low, which is slightly insufficient compared with Example 1.
[0078] Example 4 The preparation method of the carbon-supported platinum-cobalt intermetallic compound catalyst of Example 4 is basically the same as that of Example 1, except that the graphitized carbon used for loading in Example 4 is replaced by porous KB600. The prepared KB600-supported platinum-cobalt intermetallic compound catalyst of Example 4 was subjected to STEM test and XRD test. The STEM test results are shown in FIG. Figure 8 As shown in the figure, it can be seen that the particles are evenly distributed on the surface of graphitized carbon. The carbon carrier is loaded with platinum-cobalt intermetallic compound particles, and a thin layer of carbon layer is completely coated on the surface of the particles. Fig. 9 As shown, electron microscopy shows that the particles are uniformly distributed, but the degree of order is slightly lower than that of Example 1 using graphitized carbon.
[0079] Comparative Example Comparative Example 1 The preparation method of the graphitized carbon-supported catalyst of Comparative Example 1 comprises the following steps: Platinum acetylacetonate, cobalt acetylacetonate and graphitized carbon were dispersed in 7 ml of acetone by ultrasonication; the platinum loading was controlled to be 30 wt %, and dried by rotary evaporation. After drying and removing acetone, a precursor of Comparative Example 1 was obtained; The precursor was annealed in a hydrogen and argon atmosphere at 700°C for 6 hours, and after cooling, it was placed in 0.25 mol / L sulfuric acid and pickled at 60°C for 12 hours. After pickling, the catalyst was washed with deionized water and then dried in a vacuum oven at 65 degrees. After drying, it was annealed in a hydrogen and argon atmosphere at 200°C for 1.5 hours to obtain the graphitized carbon-supported platinum-cobalt intermetallic compound catalyst of Comparative Example 1.
[0080] The raw materials and preparation method of Comparative Example 1 are basically the same as those of Example 1, except that the precursor of Comparative Example 1 does not undergo the first annealing treatment in air atmosphere. The graphitized carbon supported catalyst prepared in Comparative Example 1 was subjected to STEM test and XRD test. The particle distribution and electron microscope images taken by STEM are shown in Figures 1 and 2. Fig.10a and Fig.10b As shown, through STEM, it can be seen that the particles are evenly distributed, and a layer of carbon layer is fully covered on the surface of the particles. Compared with the carbon layer in Example 1, the thickness is more than 5nm. The XRD test results are as follows Fig.11 As shown, it can be found that the material order of the sample that has not been annealed is lower, resulting in its activity being far inferior to that of the example that has been annealed in air.
[0081] Comparative Example 2 The commercial Pt / C catalyst with a platinum loading of 40 wt% and a loading of 20.0 μg Pt / cm 2 .
[0082] The graphitized carbon-supported platinum-cobalt intermetallic compound catalyst of Example 1 and the commercial Pt / C catalyst of Comparative Example 2 were subjected to the same activity test as in Example 2. The activity test results are shown in FIG. Fig.12 As shown, by comparing the polarization curves of the graphitized carbon-supported platinum-cobalt intermetallic compound catalyst and the commercial Pt / C catalyst, it can be found that the MA of the catalyst pretreated by annealing in air in Example 1 of the present application is as high as 3162mA / mgPt, while the MA of the commercial Pt / C catalyst is 430mA / mgPt. By comparing the results, it can be found that the MA of the graphitized carbon-supported platinum-cobalt intermetallic compound of Example 1 of the present application is 7-8 times that of the commercial platinum-carbon catalyst. The platinum-based intermetallic compound catalyst prepared by the preparation method of the present application has a significant activity advantage.
[0083] The KB600 supported platinum-cobalt intermetallic compound catalyst of Example 4 and the commercial Pt / C catalyst of Comparative Example 2 were subjected to the same activity test as in Example 2. The activity test results are as follows: Fig.13 As shown, by comparing the polarization curves of the platinum-cobalt intermetallic compound catalyst supported by KB600 and the commercial Pt / C catalyst, it can be found that the MA of the catalyst of Example 4 of the present application after annealing pretreatment in air is as high as 2030mA / mgPt, while the MA of the commercial Pt / C catalyst is 400mA / mgPt. By comparing the results, it can be found that the activity is still much higher than that of the commercial platinum-carbon catalyst. The platinum-based intermetallic compound catalyst prepared by the preparation method of the present application has a significant activity advantage.
[0084] The graphitized carbon-supported platinum-cobalt intermetallic compound catalyst of Example 1 and the graphitized carbon-supported catalyst of Comparative Example 1 were subjected to the same activity test as in Example 2. The activity test results are as follows: Fig.14 As shown. It can be found that the specific MA of the unannealed comparative example 1 is 882mA / mgPt, which is lower than that of Example 1. The electrochemical performance of the comparative example 1 with a thicker carbon layer is lower than that of Example 1. It can be seen that the properties of the carbon layer will affect the electrochemical activity, and the porosity of the carbon layer of the comparative example 1 is lower than that of the example 1, which also shows that the pre-oxidation treatment in the air of the present application can improve the activity of the catalyst. The specific activity value bar comparison chart of Example 1, Comparative Examples 1 and 2 is shown in Fig.15 As shown, Example 1 has good electrochemical performance, and the loose and porous carbon layer has a good electrochemically contactable area. The preparation method provided in this application can effectively improve the catalyst activity.
[0085] It should be understood that the application of the present application is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made according to the above description, and all these improvements and changes should fall within the scope of protection of the present application.
Claims
1. A method for preparing a carbon-supported metal catalyst, characterized in that: The following steps are involved: Platinum acetylacetonate, acetylacetonate of a transition metal and a carbon material are dispersed in a solvent, the solvent is removed by drying to obtain a precursor, and a mixture is obtained after a first annealing in an air atmosphere; The mixture is annealed for a second time in a hydrogen and argon atmosphere, acid-washed after cooling, washed and dried, and annealed for a third time in a hydrogen and argon atmosphere to obtain the carbon-supported metal catalyst.
2. The method for preparing a carbon-supported metal catalyst according to claim 1, characterized in that: The temperature of the first annealing is 100-500°C, and the annealing time is 5-500min; The weight loss rate of the mixture before and after the first annealing is 1-50%wt.
3. The method for preparing a carbon-supported metal catalyst according to claim 2, characterized in that: The first annealing temperature is 176°C and the annealing time is 20-40min; The weight loss rate of the mixture before and after the first annealing is 1-30%wt.
4. The method for preparing a carbon-supported metal catalyst according to claim 1, characterized in that: The second annealing condition is annealing at 400-1100° C. for 10 min-8 h.
5. The method for preparing a carbon-supported metal catalyst according to claim 4, characterized in that: The pickling conditions are pickling in sulfuric acid with a concentration of 0.1-1 mol / L at 60° C. for 12 hours.
6. The method for preparing a carbon-supported metal catalyst according to claim 1, characterized in that: The third annealing condition is annealing at 100-500° C. for 10 min-6 h.
7. The method for preparing a carbon-supported metal catalyst according to claim 1, characterized in that: The carbon material includes graphitized carbon or commercial carbon material; The graphitized carbon is prepared by heating an amorphous carbon material at 1200-3000° C. for 10 min-6 h in an inert atmosphere or a nitrogen atmosphere, and then naturally cooling to room temperature; The commercial carbon material is one of Vulcan XC72, KB300, KB600, BP 2000 or Toray carbon.
8. The method for preparing a carbon-supported metal catalyst according to claim 1, characterized in that: The transition metal acetylacetonate is one or more of iron acetylacetonate, nickel acetylacetonate, molybdenum acetylacetonate, vanadium acetylacetonate, copper acetylacetonate, manganese acetylacetonate, zinc acetylacetonate, titanium acetylacetonate, tungsten acetylacetonate, chromium acetylacetonate and zirconium acetylacetonate.
9. The method for preparing a carbon-supported metal catalyst according to claim 1, characterized in that: The platinum loading in the carbon-supported metal catalyst is 1-60 wt %.
10. A carbon-supported metal catalyst, characterized in that: It includes a carbon carrier on which metal nanoparticles are distributed and loaded, and the surface of the metal nanoparticles is coated with a carbon layer; The carbon carrier is a solid nanoparticle or a porous continuous structure, and the particle size of the solid nanoparticle is 1nm-300μm; The particle size of the metal nanoparticles is 1-20 nm; The pore structure in the carbon layer is one of loose porous, microporous or closed non-porous; The coating is one of no coating, partial coating or full coating; The thickness of the carbon layer is 0.001 -50nm; The number of the carbon layers is 0-50.
Citation Information
Patent Citations
Carbon-coated alloy PtCo based on vapor etching and preparation method and application thereof
CN118610500A
Nitrogen-containing carbon material, method for manufacturing the same and electrode for fuel cell
JP2014097912A
Supported platinum catalyst and manufacturing method of the same
US20160372759A1
Cited By
Lead-modulated high-poisoning-resistance intermetallic compound bifunctional catalyst as well as preparation method and application thereof
CN120243059A
Carbon-supported metal catalyst and preparation method therefor
WO2026157588A1